HUBUNGAN KARAKTERISTIK DENGAN TINDAKAN IBU RUMAH TANGGA DALAM PENCEGAHAN PENYAKIT MALARIA DI DESA SORIK KECAMATAN BATANG ANGKOLA KABUPATEN TAPANULI SELATAN TAHUN 2012 - seri astuti; Eddy Syahrial; Alam Bakti (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2013)
ABSTRACT Malaria is one of transmitted diseases and as the problem for the society. The most effective prevention to malaria is by involving the society through the found is regarding lack of participation of the society in the implementation of malaria management activity. The objective of this research is to know the relationship of the characteristics with action of the mothers in the prevention of malaria in Sorik Village, Batang Angkol sub-district, South Tapanuli regency. This research was analytic with cross sectional approach. The population was all household women residing in Sorik Village, Batang Angkol sub-district for 77 persons. The data of the characteristis (age, education, accupation), knowledge, attitude and action were obtained through interview using questionnaire. The collected data was then analyzed with Chi-Square with α = 0.05. The results of research showed that statistically, the variable of education (p value = 0.032), knowledge (p value = 0.000) and attitude (p value = 0.000) had significant influence to age and status did not have significant influence to the action in the prevention of malaria disease. It is suggested for health providers in Community Health Centre to give information about malaria for the society. The information should not be given only through interview or leaflet distribution, but also in real action such as mutually working to get real advantages form the information.